2018
DOI: 10.1155/2018/4941605
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Traffic Environmental Vision Pressure on Driver Behaviour

Abstract: Car-following (CF) and lane-changing (LC) behaviours are basic components in driving process. Previous models described them as physical processes with vehicle dynamics and physical criteria. However, drivers’ decisions are greatly influenced by their subjective vision information of various traffic environment elements. To solve this problem, we propose a new concept of traffic environmental vision pressure to explain these two behaviours. The pressure source consists of two parts: nearby vehicles and infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…earlier than others, then their psychology index (such as heart rate) would force them to react more quickly [42]. Although drivers' reactions are different, the average behaviour shows that A the field strength model can quantify the road infrastructure risk correctly; B driver behaviour will change with the risk levels of nearby road infrastructures, so it verifies the necessary of this assessment study and the importance of road infrastructure planning.…”
Section: High Risk E⩾140mentioning
confidence: 68%
“…earlier than others, then their psychology index (such as heart rate) would force them to react more quickly [42]. Although drivers' reactions are different, the average behaviour shows that A the field strength model can quantify the road infrastructure risk correctly; B driver behaviour will change with the risk levels of nearby road infrastructures, so it verifies the necessary of this assessment study and the importance of road infrastructure planning.…”
Section: High Risk E⩾140mentioning
confidence: 68%
“…Castro ( 22 ) reported that over 90% of traffic accidents are the result of human errors, among which 90% are associated with impaired visibility. Li et al ( 23 ) studied the effect of traffic environment on lane changing and car-following behavior. In particular, they proposed the notion of vision pressure, which is partly administrated by the characteristics of roadside units.…”
Section: State Of the Artmentioning
confidence: 99%
“…Mansensterbug, an American psychology professor, initiated the driver suitability test in 1912. Up to now, there are many methods to detect driver suitability in the world, including: the driver suitability test compiled by the Japanese Police Research Institute and the Police Department, the ART-90 test in Australia, the Wilson driver selection test in the United States, the TOST test in the United Kingdom, the driver test of the Institute of Traffic Medicine and Traffic Psychology in the former Yugoslavia, and the employment selection method formulated by the Gorky Institute of Health, Labor and Occupational Diseases in the former Soviet Union [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%